CLASSROOM MANAGEMENT STRATEGIES IN FOREIGN LANGUAGE CLASSROOM - Abin, Rais; Suryadi, Ray (English Language Education Study Program, 2024)
This research aimed to explore the strategies applied by EFL teachers in managing classroom. This research employed descriptive qualitative method. The subjects of this research were English teachers of seven grade at SMP Negeri 3 Wundulako which were selected through purposive sampling. The data of this research were collected by employing field note and an interview. The obtained data was analyzed in three major phases namely data reduction, data display, and conclusion. The result of the research revealed several strategies applied in the classroom management. They were classroom environment, student management, seating arrangements, and monitoring activity. To enhance the significance and applicability of these findings, the future research is expected to conduct comparative studies to analyze the differences in classroom management strategies across various educational levels (e.g., elementary, high school) or different subjects. Comparing strategies employed in EFL classrooms with those in other language classrooms may yield interesting insights.